7(7y+2)-9=-2

Simple and best practice solution for 7(7y+2)-9=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(7y+2)-9=-2 equation:


Simplifying
7(7y + 2) + -9 = -2

Reorder the terms:
7(2 + 7y) + -9 = -2
(2 * 7 + 7y * 7) + -9 = -2
(14 + 49y) + -9 = -2

Reorder the terms:
14 + -9 + 49y = -2

Combine like terms: 14 + -9 = 5
5 + 49y = -2

Solving
5 + 49y = -2

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + 49y = -2 + -5

Combine like terms: 5 + -5 = 0
0 + 49y = -2 + -5
49y = -2 + -5

Combine like terms: -2 + -5 = -7
49y = -7

Divide each side by '49'.
y = -0.1428571429

Simplifying
y = -0.1428571429

See similar equations:

| -5y-9=-y+1 | | 6(c+4c)=4c-18 | | 6x+4(4x-15)=50 | | -2=w/5 | | 3k-9=7+2k-k | | -4x+4(2x+8)=-8+8(x+8) | | L+50=1.32 | | -8/9(9+y)=64 | | 5/3x+1/3x=8/3+8/3x | | -8(t-7)-7(2t+1)=-17 | | 7(x-4)=6(x+1)-3 | | 5(40-(40-x))+10(40-x)+25x=405 | | -59=-5(4a-4)+1 | | -x-(13+4x)=-3(5-9k)+2 | | -0.8(2x-6)=1.7(3-x) | | 3y+(-11y)= | | 12x^2-81x-3/7=0 | | x/3-9=11 | | 12x^2-81x-3/7 | | -15t-9+8t=4t-3 | | 4+-1x=-1x+4 | | 0.5x-0.1=0.4-0.6(9-2x) | | 3y-7=2y+5 | | 3-6x=-80-5x | | 4+-1x=1x+4 | | x^2+1x=272 | | -2y+8=3y+28 | | 6x^24= | | 3x+1.5x+x+180=455 | | 6(4x-3)-10= | | 7x+9x-69=46-7x | | 2(9x-1)=99-7(3-4k) |

Equations solver categories